A Prototype for Monitoring the Continuing Education of Indigenous Health Professionals: A Study with the Indigenous Health Secretariat of the Brazilian Ministry of Health - Lucas Alves da Nóbrega Alberto Dantas; Vladimir Arthur Fey; Fernando Richartz; Luiza Santangelo Reis; Fabricia Silva da Rosa; Rogério João Lunkes; Ana Carolina da Costa (MDPI AG, 2024)
This study proposes a prototype (Business Intelligence) for monitoring the continuing education of indigenous health professionals in the Secretariat of Indigenous Health (SESAI) of Brazil's Ministry of Health (MS). The prototype builds on SESAI/MS staff knowledge and takes into account the characteristics and demands of the 34 Special Indigenous Health Districts (DSEIs). The prototype provides information for managing SESAI/MS continuing education in order to meet strategic goals. By improving the effectiveness and efficiency of the continuing education of professionals who serve Brazil's indigenous population, we will be acting directly on access issues and improving the quality of life of the indigenous population.